2015
DOI: 10.2350/15-07-1675-oa.1
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Neuronal Dysplasia-Like Submucosal Ganglion Cell Hyperplasia at the Proximal Margins of Hirschsprung Disease Resections

Abstract: Intestinal neuronal dysplasia type B (IND) denotes an increased proportion of hyperplastic submucosal ganglia, as resolved histochemically in 15 µm-thick frozen sections. IND has been reported proximal to the aganglionic segment in patients with Hirschsprung disease (HSCR) and is putatively associated with a higher rate of post-surgical dysmotility. We have developed and validated histological criteria to diagnose IND-like submucosal ganglion cell hyperplasia (IND-SH) in paraffin sections, and used the approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 44 publications
0
14
0
2
Order By: Relevance
“…In the latter scenario, it has been proposed to cause persistent obstructive symptoms after pullthrough surgery [12] but whether this is true is debated. [13] IND remains a controversial entity, with some suggesting that its histologic features are secondary to chronic obstruction rather than a primary cause of constipation. Regardless, treatment is similar to that of chronic constipation, with some severe cases requiring surgery, including sphincterotomy, diverting colostomy, or colectomy.…”
Section: Intestinal Neuronal Dysplasiamentioning
confidence: 99%
“…In the latter scenario, it has been proposed to cause persistent obstructive symptoms after pullthrough surgery [12] but whether this is true is debated. [13] IND remains a controversial entity, with some suggesting that its histologic features are secondary to chronic obstruction rather than a primary cause of constipation. Regardless, treatment is similar to that of chronic constipation, with some severe cases requiring surgery, including sphincterotomy, diverting colostomy, or colectomy.…”
Section: Intestinal Neuronal Dysplasiamentioning
confidence: 99%
“…The most recent study on this subject was from Gálvez et al [62] (2004) who identified histopathological changes suggestive of INDB in some adult rats in a model of chronic colonic obstruction. An association between INDB and HD has also been reported [8,35,6365] . In such cases, the segments proximal to the aganglionic obstructed segment present histological characteristics of INDB [6,54] .…”
Section: Pathogenesismentioning
confidence: 88%
“…IND proximal to a segment of aganglionosis is not uncommon and has been suggested to be a possible cause of persistent bowel problems after surgery for HD. This association may occur in 6% to 44% of HD patients [5,28,34,35] .…”
Section: Epidemiologymentioning
confidence: 99%
“…One formalin-fixed, paraffin-embedded approach to assess IND B-like submucosal ganglion cell hyperplasia was published by Swaminathan and colleagues 24 in 2014. Ganglion cell bodies were immunolabeled with an antibody specific for the Hu C/D antigen, which specifically and robustly localizes to the cell bodies of all enteric neurons.…”
Section: Changes In Diagnostic Criteriamentioning
confidence: 99%
“…This may be one reason for the age-related decline in submucosal ganglion size during infancy and early childhood. 24,25 In the context of these dynamic changes in ganglionic morphology, section thickness will also affect ganglion cell counts, and therefore must be standardized.…”
Section: Inappropriate Extrapolation Of 1990 Frankfurt Consensus or 2mentioning
confidence: 99%